The Responsibility of the Guardian for the Transfer of Land Rights to the Children Due to Instruction - Larasati Larasati; Siti Ummu Adillah; Peni Rinda Listyawati (Sultan Agung Notary Law Review, 2022)
The results in the emergence of rights and obligations for a person as well as the emergence of law between children, parents and the surrounding community. A child has the right and authority as a legal subject. Children have an important role in a marriage bond, apart from being the hope of parents, children also act as successors of offspring. Children in general are a group of people who are immature, unmarried and incapable of acting for themselves. The purpose of this paper is to determine the implementation of the transfer of land rights and responsibilities to minors due to inheritance. This study uses a sociological juridical approach, which is carried out by field research aimed at the application of law. This research specification uses descriptive analysis, namely research which in addition to providing an overview, writing and reporting an object or an event will also draw general conclusions from the existing problem. The data sources of this study are primary data sources and secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Methods of data collection using interviews, document studies and library materials. While the data analysis used qualitative analysis. The results of the study show thatthe implementation of the transfer of land rights to minors must apply for the determination of child guardianship and a permit to sell at the Religious Courts for Muslims and the District Courts for non-Muslims as one of the administrative requirements. After the decision on the guardianship determination has been issued by the local court, it can be used as a basis for the transfer of land rights by sale and purchase owned by minors due to inheritance.In the transfer of inheritance rights to land owned by minors, they cannot be freely transferred by their parents, they must comply with and comply with the applicable legal regulations in the transfer of inheritance of minors. The responsibility of the guardian towards minors due to inheritance is that the guardian is obliged to carry out his obligations to take care of the children who are under his control and all property as well as possible. The guardian is obliged to make a list of the child's property under his control and record all changes in the child's property.